Medication Profiles of Patients in the University of Puerto Rico Inflammatory Bowel Disease Registry - Melendez, Jorge David; Larregui, Yaritza; Vázquez, Jewel M.; Carlo, Víctor L.; Torres, Esther A. (Puerto Rico Health Sciences Journal, 2011)
Objective: The prevalence of inflammatory bowel disease [IBD, Crohn’s disease (CD) and ulcerative colitis (UC)] in Puerto Rico has increased significantly in recent years. Experience with these diseases outside of a referral center is limited. A registry for IBD, created by the University of Puerto Rico (UPR) Center for IBD, has collected data from subjects all over the island for 15 years. We analyzed the medication profiles and IBD-related surgeries of the registrants in order to characterize the therapies used and to identify any trends in disease severity. Methods: This descriptive study reports on the medication profiles of 507 individuals with IBD (1995 to 2007). Descriptive statistics related to gender, diagnosis, pharmacological therapies (aminosalicylates, steroids, immune modulators, and anti-TNF antibodies), and IBD-related surgical interventions (as indicators of disease severity) are presented. Results: The study included 256 females and 251 men. There were 241 patients with UC (48%) and 266 patients with CD (52%). The great majority of them had received aminosalicylates and steroids. Biological agents and immune modulators were less commonly used, generally in IBD patients who had undergone surgical procedures. Steroid use was almost equivalent in both IBD populations despite a trend towards greater steroid use both in UC patients with colectomies and in nonsurgical CD patients. Conclusion: Aminosalicylates and steroids are the mainstays of medical treatment for IBD in Puerto Rico. The use of biological agents and immune modulators appears to be limited to severe disease. A prospective analysis to detect changes in prescribing practices, as a step-down approach becomes more prevalent, is needed.